Biomechanical Risk Factors Associated with Running-Related Injuries: A Systematic Review - Ceyssens, Linde; Vanelderen, Romy; Barton, Christian; Malliaras, Peter; Dingenen, Bart (Sports medicine (Auckland), 2019)
Background Running is a popular form of physical activity with many health benefits. However, the incidence and prevalence of running-related injuries (RRIs) is high. Biomechanical factors may be related to the development of RRIs. Objective This systematic review synthesizes biomechanical risk factors related to the development of RRIs in non-injured runners. Methods PubMed, Web of Science, CINAHL, Embase, and SPORTDiscus were searched in July 2018 for original peer-reviewed prospective studies evaluating potential biomechanical factors associated with the development of RRIs. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Two reviewers independently assessed articles for inclusion and methodological quality. Due to methodological heterogeneity across studies, a narrative synthesis of findings was conducted, rather than a meta-analysis. Results Sixteen studies, including 13 of high quality and three of moderate quality, were included. A large number of biomechanical variables were evaluated, producing inconsistent evidence overall. Limited evidence indicated greater peak hip adduction in female runners developing patellofemoral pain and iliotibial band syndrome, but not for a mixed-sex population of cross-country runners sustaining an RRI. The relationship between vertical loading rate and RRIs was inconsistent. Other kinematic, kinetic and spatiotemporal factors were only studied to a limited extent. Conclusions Current prospective evidence relating biomechanical variables to RRI risk is sparse and inconsistent, with findings largely dependent on the population and injuries being studied. Future research is needed to confirm these biomechanical risk factors and determine whether modification of these variables may assist in running injury prevention and management.